4CPS-255 Frequency of consumption of complementary and alternative medicine among HIV patients: a multicentre cross-sectional study. (22nd April 2022) - Gonzalez Colominas, E; De Antonio Cuscó, M; Masip Torne, M; Martin, M; Cardona, G; Comas, M; Roch, MA; López, B; Torres, FI; Retamero, A; Luque, P
Abstract : Background and importance: Consumption of complementary and alternative medicine (CAMs) has increased among human immunodeficiency virus (HIV) patients. CAMs are of questionable safety and efficacy and may interact with antiretroviral treatment (ART). There are no data about the frequency of CAMs consumption in the Spanish HIV population. Aim and objectives: This study aimed to explore CAMs consumption and drug-drug interactions (DDI) in a cohort of HIV patients. Material and methods: Cross-sectional multicentre study conducted between June and November 2018 in nine Spanish hospitals. Data collected: demographics, current ART, adherence (patients' self-report), CAMs consumption, virological and immunological current status. A structured questionnaire was used to assess CAMs consumption. Identification of DDI was performed using the University of Liverpool database and classified in three categories: no clinically significant interaction, potential interaction requiring close monitoring/change (moderate) and contraindication (severe). Results: 420 patients were included; 347 (82.6%) male, aged 47(±10.4) years; 337 (80.2%) Caucasian, 209 (49.8%) taking 86 different CAMs. Table 1 shows the characteristics of patients taking CAMs and the most consumed CAMs. Ninety (21.4%) patients took ≥3 CAMs and 34 (8.1%) took ≥5 CAMs. At least one DDI was identified in 34 (16.3%) patients, all being moderate. Most frequent CAMs involved in DDI were magnesium (n=8), multivitamins (n=7) and cat's claw (n=3). In 68 (79.1%) CAMs no information was found. Conclusion and relevance: A high frequency and variety of CAMs consumption was observed in the Spanish HIV population, with green tea, black tea, red tea, fish oil and ginger being the most consumed products. In 16% of patients a DDI with the ART requiring close monitoring/treatment change was detected. However, in almost 80% of CAMs no information about potentials DDI was found. These results highlight the need to provide adequate information about these products to HIV patients as part of their pharmaceutical care due to their unawareness of potential drug interactions. References and/or acknowledgements: Conflict of interest: No conflict of interest